PERILAKU MASYARAKAT MENGKONSUMSI MINUMAN KERAS YANG MENYEBABKAN KRIMINALITAS DI KELURAHAN WATULAMBOT KECAMATAN TONDANO BARAT - Muhammad Fajar Hidayat; Puteri Dewi Sari Pinem; Yesika Sapira BR Sembiring; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2022)
This study aims to find out how the behavior of alcohol users in Watulambot Village, West Tondano District and what causes users to fall into liquor. The research method used in this research is a qualitative method with a descriptive approach with data collection techniques, observation and direct interviews with informants. The results of the study showed that the behavior of liquor users in the Watulambot sub-district, Tondano Barat sub-district, was when the users had drunk or the deviant behavior was carried out, namely fighting, assaulting, and committing domestic violence. And as for the causes of users falling into liquor in the Watulambot sub-district, namely due to frustration, a culture of drinking, and association